Solitons and complexitons to the (2+1)-dimensional Heisenberg ferromagnetic spin chain model - Aliyu, Aliyu Isa; Li, Yongjin; İnç, Mustafa; Baleanu, Dumitru; Alshomrani, Ali S. (World Scientific Publ Co Pte Ltd, 2019)
This paper investigates the (2 + 1)-dimensional Heisenberg ferromagnetic spin chain (HMF) model. The model describes the nonlinear spin dynamics of HMF. By adopting the modified F-Expansion and projective Riccati equation methods, we report the dark, combined dark-bright and envelope optical solitons, complexitons singular solutions of the equation along with the conditions that must be satisfied for solitons to exist. The physical structure of the obtained solutions are shown by graphic illustration in order to give a better understanding on the dynamics of optical solitons.
Keywords: Optical solitons; Heisenberg ferromagnetic spin chains; modified F-Expansion method; projective Riccati equation method